Structure-property relationships in alkoxy substituted benzoates from experimental and computational thermochemistry - Sergey P. Verevkin; Ruslan N. Nagrimanov; Vladimir V. Turovtsev (Chemical Thermodynamics and Thermal Analysis, 2023)
The energetics of formation and the phase transitions for isomeric methyl and ethyl methoxy‑benzoates were studied. The vapour pressures of methyl 2‑methoxy-benzoate and methyl 4‑methoxy-benzoate were measured by transpiration method. The high-precision combustion calorimetry was used to derive the liquid-phase enthalpy of formation of methyl 2‑methoxy-benzoate. The new results and the data available in the literature were critically evaluated using the structure-property correlations. Reliable correlations were established between the vaporisation enthalpies and the normal boiling temperatures as well as with the Kovats indices. Moreover, the validity of vaporisation enthalpies of alkyl methoxy‑benzoates was proved using structure-property relationships within families of structurally similar molecules. Mutual validation of the experimental and theoretical gas phase enthalpies of formation was performed using high-level quantum-chemical methods. The enthalpic contributions to the enthalpy of formation in the gas phase, resulting from the nearest and non-nearest neighbour interactions of the substituents in the benzene ring, were developed and used to quantify the intra-molecular hydrogen bond strength in the ortho-substituted species.